2017
DOI: 10.18632/oncotarget.22503
|View full text |Cite
|
Sign up to set email alerts
|

Sodium taurocholate cotransporting polypeptide (NTCP) deficiency: Identification of a novel SLC10A1 mutation in two unrelated infants presenting with neonatal indirect hyperbilirubinemia and remarkable hypercholanemia

Abstract: Sodium taurocholate cotransporting polypeptide (NTCP) is encoded by the gene SLC10A1 and expressed in the basolateral membrane of the hepatocyte, functioning to uptake bile acids from plasma. Although SLC10A1 has been cloned and NTCP function studied intensively for years, clinical description of NTCP deficiency remains rather limited. This study reported the genotypic and phenotypic features of two neonatal patients with NTCP deficiency. They both presented with neonatal indirect hyperbilirubinemia and remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The bile salt cycle is called enterohepatic circulation [17]. Due to the impaired function of sodium-dependent bile acid in hepatocytes of patients with NTCPD; thus, these patients could have plasma bile acid is increased and jaundice [10,14]. In this case, the patient appeared jaundiced after birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bile salt cycle is called enterohepatic circulation [17]. Due to the impaired function of sodium-dependent bile acid in hepatocytes of patients with NTCPD; thus, these patients could have plasma bile acid is increased and jaundice [10,14]. In this case, the patient appeared jaundiced after birth.…”
Section: Discussionmentioning
confidence: 99%
“…We provide information about NTCPD to alleviate their anxiety. The primary manifestations of NTCPD are persistently high TBA [10], neonatal jaundice [12], and fat-soluble vitamin deficiency [4]. In addition, some female patients will have increased TBA during pregnancy [7].…”
Section: Psychological Carementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we decided to select two carriers from the SLC10 carrier family, which are more unique in the sense of substrate specificity and tissue expression and which both show sodium-dependent transport of sulfated steroids (15,26). In both carriers, genetic variants or mutations were described before with significantly reduced transport activity, associated with increased plasma levels of their substrates (27)(28)(29)(30). However, as the determination of DHEAS serum levels is not included in standard diagnostics, elevated DHEAS levels may have been overseen in patients with such carrier defects.…”
Section: Case Presentationmentioning
confidence: 99%
“…Although the gene SLC10A1 was cloned as early as in 1994 (Hagenbuch and Meier 1994) while NTCP function has been studied extensively (Ho et al 2004;Yan et al 2012Yan et al , 2014, the first patient with NTCP deficiency was just reported in 2015 as a homozygote of the SLC10A1 variant c.755G>A(p.Arg252His) (Vaz et al 2015). Thereafter, only a limited number of such patients harboring biallelic pathogenic SLC10A1 variants including c.800C>T(p.Ser267Phe), c.263T>C(p.Ile88Thr) and c.615_618del (p.Ser206Profs*12) have been reported (Deng et al 2016;Liu et al 2017;Qiu et al 2017;Song and Deng 2017;Van Herpe et al 2017;Tan et al 2018), while the clinical features of NTCP deficiency remained far from being well understood. In this paper, five patients with NTCP deficiency were diagnosed via SLC10A1 analysis in two unrelated families.…”
Section: Introductionmentioning
confidence: 99%